2017
DOI: 10.1186/s12880-017-0200-1
|View full text |Cite
|
Sign up to set email alerts
|

Semi-automatic synthesis and biodistribution of N-(2-18F-fluoropropionyl)-bis(zinc (II)-dipicolylamine) (18F-FP-DPAZn2) for AD model imaging

Abstract: BackgroundPhosphatidylserine (PS)-targeting positron emission tomography (PET) imaging with labeled small-molecule tracer is a crucial non-invasive molecule imaging method of apoptosis. In this study, semi-automatic radiosynthesis and biodistribution of N-(2-18F-fluoropropionyl)-bis(zinc(II)-dipicolylamine) (18F-FP-DPAZn2), as a potential small-molecule tracer for PET imaging of cell death in Alzheimer’s disease (AD) model, were performed.Methods 18F-FP-DPAZn2 was synthesized on the modified PET-MF-2V-IT-I syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…This was consistent with previous research, which showed that the low absolute uptake of two 99m Tc-labeled Zn 2+ -DPA coordination complexes in the injured myocardium might be less detectable by SPECT imaging . Overall, both the PET and SPECT probes based on Zn 2+ -DPA complexes showed low to moderate uptake in the target tissues and high uptake in the abdomen. Therefore, further structural modification to enhance PS-binding affinities of Zn 2+ -DPA-based molecular probes as well as to improve their pharmacokinetic properties is essential for improving in vivo imaging performance.…”
Section: Apoptosis Imagingsupporting
confidence: 90%
See 1 more Smart Citation
“…This was consistent with previous research, which showed that the low absolute uptake of two 99m Tc-labeled Zn 2+ -DPA coordination complexes in the injured myocardium might be less detectable by SPECT imaging . Overall, both the PET and SPECT probes based on Zn 2+ -DPA complexes showed low to moderate uptake in the target tissues and high uptake in the abdomen. Therefore, further structural modification to enhance PS-binding affinities of Zn 2+ -DPA-based molecular probes as well as to improve their pharmacokinetic properties is essential for improving in vivo imaging performance.…”
Section: Apoptosis Imagingsupporting
confidence: 90%
“…In contrast, 18 F-FDG exhibited no significant change in tumor uptake between doxorubicin-treated mice and untreated mice . The same research group subsequently prepared a structurally similar probe named 18 F-FP-DPAZn2 and developed a semiautomatic synthetic method. , The potential of 18 F-FP-DPAZn2 for imaging apoptosis was confirmed in rats with acute myocardial infarction and in mice with Alzheimer’s disease. , However, whether this probe can be used for imaging of tumor apoptosis following anticancer treatment has not been investigated.…”
Section: Apoptosis Imagingmentioning
confidence: 99%
“…Fujiwara et al described the analogous N -[ 18 F]­fluoroacetyl- d -glucosamine with imaging in a murine tumor model showing moderate bone uptake . We therefore decided to acylate muramic acid with 4-nitrophenyl 2-[ 18 F]­fluoropropionate ([ 18 F]­NFP), , to validate the NAM-derived diastereomers ( S )-[ 18 F]­FMA and ( R )-[ 18 F]­FMA for imaging bacterial infection. Successful use of N -acylation for NAM radiolabeling would also motivate new methods for 18 F-incorporation into NAc mimics that can be applied to various metabolites of biochemical/medicinal interest.…”
mentioning
confidence: 99%